2022
DOI: 10.3390/cancers14061592
|View full text |Cite
|
Sign up to set email alerts
|

Targeting an MDM2/MYC Axis to Overcome Drug Resistance in Multiple Myeloma

Abstract: Background: MDM2 is elevated in multiple myeloma (MM). Although traditionally, MDM2 negatively regulates p53, a growing body of research suggests that MDM2 plays several p53-independent roles in cancer pathogenesis as a regulator of oncogene mRNA stability and translation. Yet, the molecular mechanisms underlying MDM2 overexpression and its role in drug resistance in MM remain undefined. Methods: Both myeloma cell lines and primary MM samples were employed. Cell viability, cell cycle and apoptosis assays, siRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…On the other hand, recently, a new approach has been taken to overcome the XIAP upregulation by using a novel Mdm2/XIAP dual inhibitor called MX69 [57, 58]. It is shown to have a robust cytotoxic effect in tumour cells by blocking the physical interaction between Mdm2 and XIAP mRNA, inhibiting IRES-dependent translation of XIAP [57, 58].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, recently, a new approach has been taken to overcome the XIAP upregulation by using a novel Mdm2/XIAP dual inhibitor called MX69 [57, 58]. It is shown to have a robust cytotoxic effect in tumour cells by blocking the physical interaction between Mdm2 and XIAP mRNA, inhibiting IRES-dependent translation of XIAP [57, 58].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, recently, a new approach has been taken to overcome the XIAP upregulation by using a novel Mdm2/XIAP dual inhibitor called MX69 [57, 58]. It is shown to have a robust cytotoxic effect in tumour cells by blocking the physical interaction between Mdm2 and XIAP mRNA, inhibiting IRES-dependent translation of XIAP [57, 58]. To further validate our model, we examined the effect of the inhibitor MX69 on the cell outcomes by displaying the levels of active caspase-3 and XIAP driven by the XIAP induction strength ( k 24 ) when D ≥ 0.065 mM (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…6 Several studies have shown that compared to normal subjects, both newly treated MM patients and recurrent MM patients have higher levels of c-Myc expression. 18 Therefore, c-Myc could be an effective target for the treatment of MM. Despite the continuous emergence of new treatment options that have improved the survival rate of MM patients, MM remains an incurable disease with high resistance and recurrence rates.…”
Section: Discussionmentioning
confidence: 99%
“…MDM2 is elevated in MM and is key to MM growth and survival ( 62 ). Targeting an MDM2/MYC axis could overcome drug resistance in MM ( 63 ). GSK3β could activate the βcatenin pathway in MM cells and promotes the malignancy of MM ( 64 , 65 ).…”
Section: Discussionmentioning
confidence: 99%